The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ijom.2017.02.419
|View full text |Cite
|
Sign up to set email alerts
|

Non-smoking, non-drinking elderly females, a five-year follow-up of a clinically distinct cohort of oral squamous cell carcinoma patients

Abstract: Background: The most common flap complication that causes flap failure is mainly due to venous thrombosis. Double venous anastomoses have been advocated in reducing the risk of venous compromise and flap failure. However, this procedure still remains controversial. Objective: The author conducted a cumulative meta-analysis to determine the benefits of double venous anastomoses in head and neck reconstruction. Methods: A literature search was conducted in accordance to the PRISMA checklist. Odds ratio (OR) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Further, five studies observed that this site predilection tallied with the age distribution. 11,19,20,23,27 Younger NSND patients were found to have anterior tongue carcinomas commonly while more gingivobuccal tumors were often observed among elderly patients. This stratification was even more marked for NSND women than men.…”
Section: Demography and Clinicopathologic Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…Further, five studies observed that this site predilection tallied with the age distribution. 11,19,20,23,27 Younger NSND patients were found to have anterior tongue carcinomas commonly while more gingivobuccal tumors were often observed among elderly patients. This stratification was even more marked for NSND women than men.…”
Section: Demography and Clinicopathologic Characteristicsmentioning
confidence: 95%
“…Three of these studies observed markedly a higher proportion of white patients in the NSND than SD group. 27,30,31,33 The anterior tongue (ICD-10-C02) and gingivobuccal mucosa (ICD-10-C03, C06.0) were the two most common oral cavity subsites for tumor occurrence among NSND patients in most studies 11,19,20,22,23,27,[32][33][34] with a significantly higher proportion of tumors in these anatomic sites than SD patients (Table 2). Further, five studies observed that this site predilection tallied with the age distribution.…”
Section: Demography and Clinicopathologic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A meta-analysis of 26 articles with a total of 2532 oral cancer patients (not limited to the oral cavity) found that those with PD-L1 overexpression had lower disease-specific and disease-free survival; these patients also tend-ed to be females, NS, and/or ND. 74 Others have found a higher rate of recurrent/persistent disease and poorer 5-year survival in elderly NSND women vs SD male and female age-matched controls, 23 and proposed that elderly NSND females, 24 or young NSND patients 75 constitute a clinically distinct subset of OCSCC. Interestingly, NSND patients tend to develop malignancies at different histological sites than SD individuals, with more tumors located in the cheek mucosa and alveolar ridge, which also suggests different clinical behavior.…”
Section: Clinical Behaviormentioning
confidence: 99%
“…As such, molecular changes that drive the tumorigenesis in NSND patients remain scarce. Although more recently several studies have attempted to evaluate the clinical characteristics of OCSCC in non-smoking (NS) patients, 10,[23][24][25] the clinicopathologic data regarding the frequency of such tumors and age of tumor onset are conflicting, 10,23,25,26 and relatively few molecular drivers of the progression of OCSCC in NSND patients are currently recognized. In this overview, we summarize the current state of knowledge regarding the clinicopathologic, survival, and molecu-N o n -c o m m e r c i a l u s e o n l y lar characteristics of OCSCC patients without traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%